Unlearning and relearning fresh produce markets : a study of the social and economic forces that shape the Johannesburg Fresh Produce Market - Wegerif, Marc (University of Pretoria, 2024)
Dissertation (MSocSci (Development Studies))--University of Pretoria, 2023.